MMCD Framework and Methodology for Developing m-Learning Applications - Saifudin, W. S. N.; Salam, S.; Lim, A. M. H. (2011)
The purpose of this paper is to use MMCD, a Multimedia Mobile Content Development Framework and Methodology for developing an M-Learning application. Mobile devices limitations such as small screen resolution, limited data space and slow processing speed give challenges to the developers in developing good m-learning applications. Therefore, aspects such as content design, navigation design and mobile HCI are critical and need an extra attention during the development phase. By using Flash Lite (FL) technology that was widely supported by today mobile devices, MMCD are chosen based on the characteristic of an Agile development model and the capabilities of the final output to be used on majorities of the mobile device which definitely encourage the learning activities. Focus on the object or content design and the navigation control are two development aspects that help the development of learning application via mobile device optimized.